Training differences and selection in a talent identification system - Baker, J.; Bagats, S.; Büsch, D.; Strauss, B.; Schorer, J. (Talent Development & Excellence, 2012)
Contemporary models of human expertise (e.g., Ericsson, Nandagopal, & Roring, 2009; Howe, Davidson, & Sloboda, 1998) emphasize the crucial role that experience and training play in skill acquisition. However, the value of different forms of training across development is not clear. This study compared training histories of young athletes who were selected (n = 65) during talent identification camps with athletes from the same camps who were not-selected (n = 64). As hypothesized, selected players had different training profiles than those not-selected, although these effects were restricted to females. Selected females performed more sport-specific training than their not-selected counterparts and had greater involvement in sports outside their area of expertise (i.e., non-sport-specific training). These results suggest training behaviors distinguish between skill levels even within a single step along the athlete development pathway, at least in females. Furthermore, they suggest non-specific training may have value during early athlete development. The inconsistent effects across sex groups highlight the need to control for sex in examinations of expertise development. Further work is necessary to confirm these results in other populations and integrate these findings into more comprehensive training-based models of expert performance.